O papel da socialização materna na construção das representações sociais sobre os direitos humanos - Queiroz, Pablo Vicente Mendes De Oliveira (2015)
This study aims mainly at checking the pertinence of a theoretical model that reinforces the role of socialization agents as mediators between knowledge available in sociocultural environment and the transmission or construction of Social Representations (SR) about Human Rights (HR). In order to reach this goal theoretical references concerning the four generations of HR were applied to the SR Theory and to those approaches concerning parent socialization. The theoretical model to be checked advocates that the use of verbalizations about HR by mothers is associated to the perception children have of these verbalizations and this perception is associated to the commitment of the children with the rights verbalized. The variable verbalizations of mothers was constituted by the inductive technique; the children’s perception was related to the way they understood what their mothers told them about HR; and the commitment with HR was related to the attitudinal characteristic of the representations the children constructed about HR. Besides the main goal aforementioned, other variables such as age and sex differences of the children in relation to each one of the variables approached by the model were taken into account. In order to reach these goals, 100 mothers and 100 children from 12 to 13 years and 16 to 17 years of male sex and female sex, attending private schools, answered a questionnaire containing sociodemographic questions and scales connected with the variables under study. Altogether, the results indicate that the proposed model is adequate; the verbalization of the mothers, the perception of the children and the commitment of the children with HR is higher among those between 12-13 years than among those between 16-17 years; and the highest scores among these three variables are related to uncontroversial rights. In spite of this, we noticed a slightly higher tendency of a future commitment of the children with controversial rights than the verbalization of mothers and the children’s perception of this verbalization. We believe that this result confirm the importance of socialization agents in the construction of SR about HR and that, due to the limited knowledge of younger children, there is higher verbal investment by mothers in their education, who have, therefore, higher perception of these verbalizations. The higher the level of commitment of younger children with HR, we believe that is a consequence of more intense exposition to mothers’ verbalization about these rights; greater exposition of youngsters of this age to media that often publish the principles of HR; and also recent laws that enforce the approach of themes related to HR at schools. We understand these laws have been more beneficial to younger children as the education of older ones is veered, mainly to admission exams to the university. Furthermore, we believe that children show higher level of future commitment with controversial HR when they compare the verbalization of their mothers to the perception of these verbalizations about these rights concerning the publication of controversial rights by media, by the acquisition of awareness with the aid of social movements and by the defense of these rights at school.